The role of socioeconomic factors in selected aspects of nutritional behavior of children and adolescents practicing football in a football club in Bydgoszcz - Ameryk, Monika Anna; Sikorski, Piotr; Świątkowski, Maciej; Augustyniak, Agnieszka; Szamocka, Małgorzata (Journal of Education, Health and Sport, 2017)
Nutrition habits of children should be adapted to their physiological needs, reflecting their demand for the appropriate nutrients. Nutrition of children and adolescents practicing sports is a particular challenge, much more complex than in their peers and adults. This is related not only with their intensive growth and development and different metabolism, but also with increased physical activity. A correlation between socioeconomic factors in families (parents’ poor education, unemployment and low income) and a poor health status with increased incidence of chronic psychosomatic and organic diseases has been reported. The aim of the study was to assess the impact of socioeconomic factors on selected aspects of nutritional behavior. The investigated group consisted of 100 boys aged 10–16 years, practicing football in a football club in Bydgoszcz, Poland, whose parents answered questions from the KomPAN questionnaire adopted to the Polish conditions. The obtained results were developed statistically using the Statistica 12.5 software, with Chi-squared test and the statistical significance level at p < 0.005. A significant impact of socioeconomic factors, including family economic status, on the analyzed aspects of nutritional behavior of children and adolescents practicing football in a football club in Bydgoszcz, was demonstrated. The study revealed many improper habits in the nutrition of the investigated children, which indicates the need for appropriate nutritional education at all age levels.